2005
DOI: 10.1210/jc.2004-0931
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 Gene Polymorphisms Confer the Susceptibility of Japanese Populations to Graves’ Disease

Abstract: Graves' disease (GD) is an autoimmune disorder with genetic predisposition. IL-13 is an important mediator of antiinflammatory immune responses and is expressed in the thyroid and orbit. The aim of the present study was to investigate whether IL-13 gene polymorphisms are associated with the development of GD. IL-13 gene polymorphisms were studied in Japanese GD patients (n = 310) and healthy control subjects without antithyroid autoantibodies or a family history of autoimmune disorders (n = 244). A C/T polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 40 publications
2
44
1
1
Order By: Relevance
“…Currently, the À1112 C/T polymorphism in its 5¢-flanking region has been identified as having a biological function, and has been shown to regulate gene transcription (van der Pouw Kraan et al 1999;Howard et al 2001). In addition, the association of À1112 C/T polymorphism with GD and other atopy diseases has been widely studied (Bednarczuk et al 2003;Hummelshoj et al 2003;Hiromatsu et al 2005), but the results need support from further studies. IRF1 is a member of the IRF family of transcription factors that is involved in the regulation of genes that control cell growth, differentiation and death.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the À1112 C/T polymorphism in its 5¢-flanking region has been identified as having a biological function, and has been shown to regulate gene transcription (van der Pouw Kraan et al 1999;Howard et al 2001). In addition, the association of À1112 C/T polymorphism with GD and other atopy diseases has been widely studied (Bednarczuk et al 2003;Hummelshoj et al 2003;Hiromatsu et al 2005), but the results need support from further studies. IRF1 is a member of the IRF family of transcription factors that is involved in the regulation of genes that control cell growth, differentiation and death.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic susceptibility of these diseases is thought to be polygenic. It has been reported that major histocompatibility complex (MHC) gene [3,4], cytotoxic T lymphocyte antigen-4 (CTLA-4) gene [4][5][6], thyrotropin receptor (TSHR) gene [7], PTPN22 gene [8], CD40 gene [9,10], interferon-γ (IFN-γ) gene [11], tumor necrosis factor-α (TNF-α) gene [12,13] and interleukin-13 (IL-13) gene [14] polymorphisms are associated with GD and their interactions may influence disease phenotype and severity [3]. However, their contribution to susceptibility to GO awaits confirmation.…”
mentioning
confidence: 99%
“…6,7 The IL4 gene promoter polymorphism rs2070874 (C-589T), was reported to be associated with GD from the data of a relatively small Caucasian cohort (n ¼ 236), 6 but was never confirmed through replication in the Asian population. [26][27][28][29] Similarly, claim of association was made for polymorphisms of the IL13 gene (rs1800925, C-1112T and rs20541, G2044A) in a Japanese study, 7 but not in others. 27,[30][31][32] We did not find evidence of association with GD for these three polymorphisms in our south Han Chinese cohort (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, polymorphisms in the interleukin 4 (IL4) and the interleukin 13 (IL13) gene were reported to be associated with GD 6,7 and some genes demonstrated positive association with other autoimmune disease. It has been hypothesized that common pathogenic mechanisms may be shared among autoimmune diseases, and an allele associated with one of the autoimmune diseases has an increased earlier probability of being associated with another autoimmune disease; 8,9 therefore, single-nucleotide polymorphisms (SNPs) with convincing association with other autoimmune disease should be good candidates for GD.…”
Section: Introductionmentioning
confidence: 99%